2010
DOI: 10.2139/ssrn.1703109
|View full text |Cite
|
Sign up to set email alerts
|

University Competition, Grading Standards and Grade Inflation

Abstract: We develop a model of strategic grade determination by universities distinguished by their distributions of student academic abilities. Universities choose grading standards to maximize total wages of graduates. Job placement and wages hinge on a firm's productivity assessment given a student's university, grade and productivity signal. We identify conditions under which better universities set lower grading standards, exploiting the fact that firms cannot distinguish between "good" and "bad" "A"s. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 8 publications
(1 reference statement)
1
23
0
Order By: Relevance
“…Many of the measures of performance are under the control of the HEI, and there has been concern from senior managers of universities that some measures in league tables are susceptible to 'cheating' behaviour (Rolfe 2003), and suggestion that universities are influencing data in order to raise their rankings (Hazelkorn 2015). Graduation or achievement rates, for example, can be improved by introducing better teaching (a positive effect of rankings) or by lowering standards which leads to 'grade inflation' (Johnes 2004;Popov and Bernhardt 2013;Bachan 2015;Johnes and Soo 2015). There have also been claims that students have been pressured to provide favourable responses to the National Student Survey in the UK in order to boost performance in media rankings (Newman 2008).…”
Section: Potential Effects Of Rankingsmentioning
confidence: 99%
“…Many of the measures of performance are under the control of the HEI, and there has been concern from senior managers of universities that some measures in league tables are susceptible to 'cheating' behaviour (Rolfe 2003), and suggestion that universities are influencing data in order to raise their rankings (Hazelkorn 2015). Graduation or achievement rates, for example, can be improved by introducing better teaching (a positive effect of rankings) or by lowering standards which leads to 'grade inflation' (Johnes 2004;Popov and Bernhardt 2013;Bachan 2015;Johnes and Soo 2015). There have also been claims that students have been pressured to provide favourable responses to the National Student Survey in the UK in order to boost performance in media rankings (Newman 2008).…”
Section: Potential Effects Of Rankingsmentioning
confidence: 99%
“…Arts graduates) in order to increase course enrolments (Freeman 1999). Further, it has been observed that graduates from elite 'Ivy League' universities are awarded higher grades than those from other types of US univerities and colleges (Gose 1997;Astin 1998;Kuh and Hu 1999;Healy 2001;Popov and Bernhardt 2013). The issue of grade inflation has also attracted interest in Ireland (O'Grady and Guilfoyle 2007), Canada (Dickson 1984), Australia (Marginson 1995), Germany (Bauer and Grave 2011) and Italy (Bagues, Sylos Labini, and Zinovyevaz 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The last of Achen and Thurnau's hypotheses might, by extension, be viewed as implying that more prestigious universities are, given their strong position in the market, less likely than others to succumb to the temptations of grade inflation. Yet Popov and Bernhardt () argue otherwise. They develop a model in which good universities respond to a rising demand for highly skilled workers by relaxing the conditions under which they award top grades; they do this because they are seeking to optimize employment outcomes for their graduates, and they can exploit the fact that employers are not able to distinguish between relatively strong and weak students within the top grade.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, it allows us to investigate whether there has been any further grade inflation in the UK higher education system since the early part of the last decade. In addition, we are able to perform a comparison between the conflicting findings of Achen and Thurnau () and Popov and Bernhardt () on the relationship between university quality and grade inflation.…”
Section: Literature Reviewmentioning
confidence: 99%